Estudio de factibilidad para la creación de una empresa de servicios de acompañamiento para el adulto mayor, en actividades (citas médicas, caminatas, trámites bancarios y de acompañamiento domiciliario) en la ciudad de Loja - Medina Ordóñez, Sandra Edita (2015)
The research titled "FEASIBILITY STUDY FOR THE CREATION OF A COMPANY OF SERVICES TO SUPPORT THE ELDERLY IN ACTIVITIES (appointments, hiking, PROCEDURES AND ACCOMPANYING HOUSEHOLD BANK) in the city of Loja." Our aim is to show the need for an escort Service for the Elderly in the city of Loja, at the time and during the development of the various activities carried out in their daily lives, including the most mundane can mention such as: medical appointments, banking, hiking, shopping, and other payments; as well as feeling accompanied in their homes when their children or relatives are developing their work or study activities and therefore the Company can not provide much-needed at this stage of adulthood, when the characteristic physical and psychological are decreasing with the passage of time. To make the development of this research I used methods and techniques that allowed me to collect the necessary information and data, the methods used were Deductive; Inductive; Descriptive; Analytical and Statistical. The techniques applied were direct observation; Surveys a total of 397 applied to the sample of households in the city of Loja (Urban Parishes) as potential clients, and two interviews, one with the Economist. Jail Mogrovejo Head of Planning SRI and the other with Sister. Fabiola Botero Governing and Representative of the Servants of Jesus of Charity Prairie. Market in the supply and Demand also Determined Existing unmet demand and; Per Capita Consumption averaging activities of the Elderly of 5 times 6 per month. Regarding the service, price, place, promotion and advertising used by the company was established. Within the Technical Study in relation to the size determined aspects as Capacity Installed and Used; so much so that on the basis of capacity utilization of 95%, and by an efficient and effective for the Service Accompanying process, the company "MIS ADULTOS MAYORES" will address a number of 8 employees, a total of 7,904 services 2 hours each in their first year of life. In the location of the project I established the macro and micro location will be in the parish El Sagrario based on the preference expressed in the polls and favorable location factors; engineering project detailing how is the operating process, the phases of the service itself and the distribution of office. In the Administrative study raised the establishment of the company as a limited liability company with the name "MIS ADULTOS MAYORES" formed by three partners; and in terms of organizational structure it is defined by organizational and operating manuals. The financial study indicates that for the creation of the company investing $ 12.203,49 specifying fixed assets, deferred and necessary working capital, which will be financed purely with equity is required. Financial Evaluation in the respective indicators show sustainable profitable project with a NPV of $ 49.540,05; an IRR of 88,72% which is higher than the opportunity cost of capital and where RBC $ 1.28 for every dollar invested 0.28 cents of return will be achieved; the investment is recovered in 1 year 5 months and 12 days; Sensitivity Analysis on the Variable Costs supports an 7 increase of up to 14.98%, while the Variable Income supports up to 12.10% decrease in these parameters the project is not sensitive. With regard to the Findings indicate the need for the creation of the company, in order to provide the escort service for the elderly, because there is acceptance of the creation of the company and the manifestation of that will use the service their families allowing an active and safe development, avoiding any unnecessary risks and feelings of loneliness. Recommendations entrench and support the conclusions of what should be done for the creation and implementation of the company escort services "MIS ADULTOS MAYORES" since there is demand necessary and economically profitable also would generate jobs